2020
DOI: 10.5114/fn.2020.96983
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA alleviates the damage of neurocytes by targeting GLUT1 in ischaemia reperfusion model (in vivo and in vitro experiments)

Abstract: Stroke is partial or complete brain dysfunction combined with acute cerebral circulatory disorders, and it affects millions of individuals around the world each year. A total of 70-80% of patients experience ischaemic stroke caused by disturbances in cerebral circulation, leading to cerebral ischaemia, neuronal apoptosis, and necrosis. Tanshinone IIA is a natural compound extracted from Salvia miltiorrhiza and has been proven to assist in recovery from cerebral ischaemia reperfusion injury. GLUT1 is ubiquitous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In vitro , mainly using Neuro-2A cells cultured in Dulbecco's modified Eagle's medium and supplemented with 10% fetal bovine serum at 37°C and humidified in a 5% CO 2 atmosphere and divided into different groups treated in different ways, pretreatment with Tanshinone I could increase cell viability of HT-22 cell following oxygen-glucose deprivation (OGD) [ 10 ]. The effect of Tanshinone IIA on cellular viability results showed that the viability was significantly increased in the Tanshinone IIA treatment group groups compared with the operation group ( P < 0.05) [ 14 ]. the PI3K/mTOR signaling pathway was activated after treatment with Tanshinone IIA by detecting the expression of GLUT1 and HIF-1a and the ratio of p-AKT/AKT, p-mTOR/mTOR, and p-HER3/HER3 in cell model using western blotting analysis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , mainly using Neuro-2A cells cultured in Dulbecco's modified Eagle's medium and supplemented with 10% fetal bovine serum at 37°C and humidified in a 5% CO 2 atmosphere and divided into different groups treated in different ways, pretreatment with Tanshinone I could increase cell viability of HT-22 cell following oxygen-glucose deprivation (OGD) [ 10 ]. The effect of Tanshinone IIA on cellular viability results showed that the viability was significantly increased in the Tanshinone IIA treatment group groups compared with the operation group ( P < 0.05) [ 14 ]. the PI3K/mTOR signaling pathway was activated after treatment with Tanshinone IIA by detecting the expression of GLUT1 and HIF-1a and the ratio of p-AKT/AKT, p-mTOR/mTOR, and p-HER3/HER3 in cell model using western blotting analysis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA , a natural component derived from Salvia miltiorrhiza (Dan-Shen in Chinese), has been proven to have therapeutic effects in cerebrovascular and cardiovascular diseases. Tanshinone IIA treatment promotes the recovery of brain function and increases neuronal viability; furthermore, the glucose concentration in the serum and cultured medium was increased, possibly regulated by an increased glucose uptake ability and activation of the PI3K/AKT/mTOR pathway ( 19 ). Sodium tanshinone IIA sulfonate is a water-soluble derivative of tanshinone IIA, which suppresses the expression of HIF-1 and hemoglobin genes via inhibition of the PI3K/AKT/mTOR pathway, thereby protecting against hypoxia in cerebral hemorrhage in zebrafish ( 20 ).…”
Section: Active Extracts Of Chinese Medicinesmentioning
confidence: 99%
“…Tanshinone IIA is extracted from the dried rhizome of Salvia miltiorrhiza Bge., and is commonly used in the treatment of cerebrovascular diseases. Tanshinone IIA can promote the recovery of cerebral ischemia-reperfusion injury, increase glucose uptake and energy supply of neurons by targeting GLUT1, and reducing the expression of inflammatory factors COX-2, IL-1β, prostaglandin E2 (PGE2) and monocyte chemoattractant protein-1 (MCP-1) [102].…”
Section: Quinonesmentioning
confidence: 99%